The preference mapping of rice bran tempe cookies - Cempaka, Laras; Saraswati, Tiara Indra; Asiah, Nurul; David, Wahyudi (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2020)
Tempe is a traditional indigenous fermentation food from Indonesia. The addition of rice bran as raw material for soybean mixture aims to improve functional properties of tempe. The sensory description and sensory mapping of four formulations rice bran tempe were measured. Seventy-five consumers were recruited to participate in the projective mapping of rice bran tempe cookies at the sensory laboratory of Universitas Bakrie, one of the private universities in Indonesia. The test consists of a descriptive evaluation of products with sensory attributes: taste, color, flavor, texture and aftertaste. Data was used to develop a preference map for rice bran tempe cookies. The cookies formulation consist of rice bran tempe without any addition (RBT1), rice bran tempe with cocoa powder (RBT2), rice bran with dates extract (RBT3), and rice bran tempe with cocoa powder and dates extract (RBT4). Results from preference mapping showed that the position for each rice bran tempe cookies formulation show differently with commercial products. The map shows RBT1 and RBT2 cookies have higher consumer preferences (elevation 40) than RBT3 cookies (elevation 30) or RBT4 cookies (elevation 20). Average overall acceptance scores for the four samples ranged from 4.37 to 4.81 on a 1-9 scale. The addition of rice bran tempe to the cookies formulation has not been accepted by the consumers due to the sensory attributes of bitter taste, dark color, aroma like animal feed, hard texture and bitter aftertaste. The presence of cocoa powder and dates extract has not been able to increase consumer preference of the tempe rice bran cookies.